The efficacy of remote ischemic conditioning in improving neurological function and short-term prognosis in acute ischemic stroke: a prospective controlled study - Huang, Peiqi; Lin, Kun; Wei, Liling; Zeng, Qiong (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the efficacy of remote ischemic conditioning (RIC) in improving neurological function and short-term prognosis in patients with acute ischemic stroke (AIS).MethodsThis randomized, controlled, single-blind study aimed to evaluate the short-term (7-day) effects of RIC on neurological function in patients with AIS. 264 AIS patients (median age 65 years, 63.3% male) with ischemic symptoms <72 h post-onset were randomly assigned to either the RIC group (n = 65) or the control group (n = 199). RIC was administered manually using a cuff sphygmomanometer, while the control group received a sham RIC treatment. Patients with cardioembolic sources or a history of prior stroke were excluded from the study. Primary outcomes were the proportion of patients with an mRS score of ≤2 at 7 days, as well as changes in the National Institutes of Health Stroke Scale (NIHSS), modified Rankin Scale (mRS), Activities of Daily Living (ADL), and Rancho Los Amigos (RLA) scores. Data were collected at baseline and 7 days post-enrollment, with in-person follow-up visits conducted by blinded clinicians.ResultsAt 7 days, the RIC group showed a significantly higher proportion of patients with an mRS score of ≤2 compared to the control group (41.5% vs. 28.1%, p = 0.043). Significant improvements were observed in the RIC group compared to the control group in NIHSS (p = 0.004) and ADL scores (p = 0.005), but not in RLA scores (p > 0.05). Binary Logistic Regression Analysis indicated that, after adjusting for baseline factors, the treatment effect of RIC remained statistically significant.ConclusionRIC treatment enhances neurological function and improves short-term prognosis in AIS patients. These findings support the potential clinical application of RIC in AIS management.